Peran Corporate Social Responsibility, Corporate Governance dan Profitabilitas: Indikasi Penghindaran Pajak Pada Sektor Pertambangan di Indonesia - Dadan Ramdhani; Yanti Yanti; Merryam Apriyanti Sitompul (Universitas Matana, 2021)
This study aims to analyze the effect of corporate social responsibility disclosure, proportion of managerial ownerships, audit committees and profitability on tax avoidance. The population of this research is mining companies listed on Indonesia Stock Exchange in 2014-2018. The samples tested in this study were 13 companies with a total of 65 samples taken based on the purposive sampling method. The data used in this study are secondary data from financial reports and annual reports. This study used multiple linear regression analysis. The results of this research showed that the audit committees and profitability had a negative significant influence on tax avoidance. In addition, the variable of managerial ownerships and corporate social responsibility had not significant influence on tax avoidance.